2016
DOI: 10.1016/j.jaip.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Utility of Urinary LTE4 in Asthma, Allergic Rhinitis, Chronic Rhinosinusitis, Nasal Polyps, and Aspirin Sensitivity

Abstract: BACKGROUND Urinary leukotriene E4 (LTE4) is a well-validated marker of the cysteinyl leukotriene pathway, and LTE4 elevation has been described in conditions such as asthma, aspirin sensitivity, and chronic rhinosinusitis (CRS). There have been a number of reports investigating the role of spot urine LTE4 to predict aspirin sensitivity; however, variability in urinary LTE4 may affect the accuracy of this approach. OBJECTIVE Here, we explored the utility of 24-hour urinary LTE4 in 5 clinical diagnoses of alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 23 publications
3
59
0
Order By: Relevance
“…This biomarker has variable concentration in spot urine samples. Recently, benefits of 24‐h urine collection were presented . In our study, Cys‐LTs were released following the ingestion of aspirin and correlated with bronchial symptoms similarly to previously reported .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This biomarker has variable concentration in spot urine samples. Recently, benefits of 24‐h urine collection were presented . In our study, Cys‐LTs were released following the ingestion of aspirin and correlated with bronchial symptoms similarly to previously reported .…”
Section: Discussionsupporting
confidence: 84%
“…Lipid mediators are especially interesting in NERD because cyclooxygenases are the pharmacological targets for NSAIDs. Elevated systemic biosynthesis of LTE 4 is a common feature of NERD . The main aim of the study was to measure the concentration of anti‐inflammatory PGE 2 and its stable degradation product, tetranor‐PGE‐M, before and after a clinically relevant oral dose of aspirin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 Follow-up studies demonstrated that Ն166 pg LTE 4 /mg creatinine indicates the presence of AERD with 89% specificity, whereas a Ն241 pg LTE 4 /mg creatinine discriminated subjects with "challenge-confirmed" aspirin sensitivity with 92% specificity. 46 Exhaled nitric oxide (FeNO) levels is used as a biomarker for assessing acute bronchospasm and for supervising asthma control over time. 44,47,48 A recent study discovered that giving low-dose aspirin (40 mg) and measuring FeNO levels 1 hour later produced a significant decrease from baseline in mean FeNO by 19% in patients with AERD.…”
Section: Biomarkers For Diagnosis Of Aerdmentioning
confidence: 99%
“…The significance of CysLT in the pathophysiology of AERD and possibly other CRSwNP patients, highlights its use as a biomarker for a distict CRS endotype . Because CysLT is metabolized and excreted through the urine, the 24‐hour urinary measurement of LTC 4 has been suggested as a means to identify CRSwNP patients who have the AERD variant . The classification of CysLT‐mediated CRS may then provide a guide toward therapy utilizing leukotriene modifiers and aspirin desensitization .…”
Section: Introductionmentioning
confidence: 99%